2012
DOI: 10.1002/app.38262
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and working mechanism of a synthetic high temperature (200°C) fluid loss polymer for oil well cementing containing allyloxy‐2‐hydroxy propane sulfonic (AHPS) acid monomer

Abstract: A polymer comprising of 2-acrylamido-2-methyl propane sulfonic acid, N, N-dimethyl acrylamide, allyloxy-2-hydroxy propane sulfonic acid (AHPS), acrylic acid, and N, N-methylene bisacrylamide was synthesized by aqueous free radical copolymerization and tested as high temperature performing fluid loss additive (FLA) in oil well cement. Successful incorporation of AHPS was confirmed and characteristic properties of the copolymer were determined using size exclusion chromatography. The FLA showed excellent water r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Currently, the conventional approach for controlling the rheology and filtration of WBMs in deep drilling is to use water-soluble biopolymers or synthetic polymers as additives. However, there are inherent shortcomings of such polymers, which are either thermally degraded or generate a very high viscosity during filtration control at high temperature (Tiemeyer and Plank, 2013;Dias et al, 2015;Wan et al, 2011;Oyewole et al, 2013;Audibert et al, 1999;Kelessidis et al, 2007). The control of rheology and filtration of hightemperature WBMs remains a key technical problem, and high-temperature tolerating water-based drilling fluids are urgently required in drilling engineering (Han et al, 2014;Kelessidis et al, 2007;Alimohammadi et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Currently, the conventional approach for controlling the rheology and filtration of WBMs in deep drilling is to use water-soluble biopolymers or synthetic polymers as additives. However, there are inherent shortcomings of such polymers, which are either thermally degraded or generate a very high viscosity during filtration control at high temperature (Tiemeyer and Plank, 2013;Dias et al, 2015;Wan et al, 2011;Oyewole et al, 2013;Audibert et al, 1999;Kelessidis et al, 2007). The control of rheology and filtration of hightemperature WBMs remains a key technical problem, and high-temperature tolerating water-based drilling fluids are urgently required in drilling engineering (Han et al, 2014;Kelessidis et al, 2007;Alimohammadi et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…The forpolymer of 2-acrylamido-tertiary-butyl sulfonic acid, allyloxy-2-hydroxy propane sulfonic acid (AHPS), N, N-dimethylacrylamide and acrylic acid (AA) was synthesized via aqueous free radical copolymerization according to a method described in the literature (Tiemeyer 2013). The chemical structure of the forpolymer is shown in Fig.…”
Section: Atbs-ahps-nndma-aa Forpolymermentioning
confidence: 99%
“…To overcome this gap, recently a graft copolymer composed of humic acid, ATBS, NNDMA and acrylic acid (AA) exhibiting high effectiveness at and above 150°C was proposed (Salami 2012). Even higher temperature stability (up to 200°C) was achieved with a forpolymer synthesized from ATBS, AHPS, NNDMA and acrylic acid utilizing N, N-methylene bisacrylamide (NNMBA) as crosslinking agent (Tiemeyer 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tiemeyer et al . reported a synthetic polymer based on allyloxy‐2‐hydroxy propane sulfonic acid which exhibits excellent fluid loss performance . Salami et al .…”
Section: Introductionmentioning
confidence: 99%
“…13 Tiemeyer et al reported a synthetic polymer based on allyloxy-2-hydroxy propane sulfonic acid which exhibits excellent fluid loss performance. 14 Salami et al described a graft copolymer which comprised side chains connected to the backbone by aqueous free radical copolymerization. The backbone was humic acid, and the lateral terpolymer chains contained the monomers of sodium 2-acrylamido-2-methylpropane sulfonate, N,N-dimethyl acrylamide, and acrylic acid.…”
Section: Introductionmentioning
confidence: 99%